HDL Particle Size Is a Critical Determinant of ABCA1-Mediated Macrophage Cellular Cholesterol Export. Issue 7 (27th March 2015) - Du, Xian-Ming; Kim, Mi-Jurng; Hou, Liming; Le Goff, Wilfried; Chapman, M. John; Van Eck, Miranda; Curtiss, Linda K.; Burnett, John R.; Cartland, Sian P.; Quinn, Carmel M.; Kockx, Maaike; Kontush, Anatol; et al.
<x xml:space="preserve">Abstract</x> Rationale: High-density lipoprotein (HDL) is a heterogeneous population of particles. Differences in the capacities of HDL subfractions to remove cellular cholesterol may explain variable correlations between HDL-cholesterol and cardiovascular risk and inform future targets for HDL-related therapies. The ATP binding cassette transporter A1 (ABCA1) facilitates cholesterol efflux to lipid-free apolipoprotein A-I, but the majority of apolipoprotein A-I in the circulation is transported in a lipidated state and ABCA1-dependent efflux to individual HDL subfractions has not been systematically studied. Objective: Our aims were to determine which HDL particle subfractions are most efficient in mediating cellular cholesterol efflux from foam cell macrophages and to identify the cellular cholesterol transporters involved in this process. Methods and Results: We used reconstituted HDL particles of defined size and composition, isolated subfractions of human plasma HDL, cell lines stably expressing ABCA1 or ABCG1, and both mouse and human macrophages in which ABCA1 or ABCG1 expression was deleted. We show that ABCA1 is the major mediator of macrophage cholesterol efflux to HDL, demonstrating most marked efficiency with small, dense HDL subfractions (HDL3b and HDL3c). ABCG1 has a lesser role in cholesterol efflux and a negligible role in efflux to HDL3b and HDL3c subfractions. Conclusions: Small, dense HDL subfractions are the most efficient mediators of cholesterol efflux, and ABCA1 mediates cholesterol efflux to small dense HDL and to lipid-free apolipoprotein A-I. HDL-directed therapies should target increasing the concentrations or the cholesterol efflux capacity of small, dense HDL species in vivo.